SCIENTIFIC THEORETICAL BASIS OF INTERNATIONAL COMPETITIVENESS (Marketing Journal, 2025)
The article analyzes the role and importance of international competitiveness in the economy, as well as some theoretical aspects of competitiveness and the categories of international competitiveness.
Keywords: globalization; competition; competitiveness; liberalization; international economic integration; labor productivity; well -being of the population